SECURE REMOTE AUTHENTICATION USING BIOMETRIC DATA WITH STEGANOGRAPHY FOR WIRELESSNETWORK. - S. M. Chougule.; Prof. S. R. Mahadik. (International Journal of Innovations in Engineering Research and Technology, 2021)
In wireless communications sensitive information is frequently exchanged, requiring remote authentication. Many authentication schemes using passwords and smart cards have been proposed. However, passwords might be forgotten and smart cards might be shared, lost, or stolen. This paper tries to givesan idea about the previous researches and authentication scheme using hybrid crypto-steganographic schemes. Remote authentication involves the submission of encrypted information, along with visual and audio cues (facial images/videos, human voice etc.)